Post-fire behavior of RC columns repaired with square hollow section steel tube and RC concrete jackets - Ahmed Rafik Belakhdar; Mohamed Salah Dimia; Mohamed Baghdadi (The Journal of Engineering and Exact Sciences)
This paper investigates numerically fire-exposed reinforced concrete (RC) columns. As a first step, the study examined the effects of exposing the columns to fire for 60 minutes according to the ISO 834 fire standard on the column's residual load-bearing capacity by considering some decisive geometrical parameters such as the column height and its cross-sectional area. The second step consisted of investigating the effectiveness of the strengthening technique utilized by incorporating composite jackets, considering different strengths of concrete, in order to improve the post-fire behavior of these columns. The results showed that the longer the column is exposed to fire, the lower its bearing capacity. However, it was also found that increasing the column cross-sectional area can reduce the percentage of load-bearing capacity. Finally, it was revealed that the strengthening method used herein allowed restoring the capacity of the columns exposed to fire for a period of one hour by up to 180%.